2014
DOI: 10.1038/ncomms6505
|View full text |Cite
|
Sign up to set email alerts
|

Biting disrupts integration to spur skull evolution in eels

Abstract: The demand that anatomical structures work together to perform biological functions is thought to impose strong limits on morphological evolution. Breakthroughs in diversification can occur, however, when functional integration among structures is relaxed. Although such transitions are expected to generate variation in morphological diversification across the tree of life, empirical tests of this hypothesis are rare. Here we show that transitions between suction-based and biting modes of prey capture, which re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 68 publications
(123 reference statements)
2
53
1
Order By: Relevance
“…However, the biting we observed in northern fur seals seemed stereotypical. In contrast, suction feeding, as observed in Steller sea lions, requires a series of morphological parts and behavioral events to be coordinated to function effectively (Collar et al, 2014). Such functional integration likely constrains skull evolution and suction feeding (Collar et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the biting we observed in northern fur seals seemed stereotypical. In contrast, suction feeding, as observed in Steller sea lions, requires a series of morphological parts and behavioral events to be coordinated to function effectively (Collar et al, 2014). Such functional integration likely constrains skull evolution and suction feeding (Collar et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, suction feeding, as observed in Steller sea lions, requires a series of morphological parts and behavioral events to be coordinated to function effectively (Collar et al, 2014). Such functional integration likely constrains skull evolution and suction feeding (Collar et al, 2014). It has been suggested that the terrestrial arctoid ancestors of pinnipedimorphs ( pinnipeds and their extinct relatives) exhibited a biting feeding mode, and biting is considered the ancestral feeding mode among extant pinnipeds (Werth, 2000a;Adam and Berta, 2002;Berta et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In other fishes, decoupling of prey capture from prey processing is a function of having two sets of jaws, oral and pharyngeal, of which the latter performs the majority of processing [44]. In some fish lineages, decoupling of anatomical modules during feeding behaviour has led to radical changes in the morphology of formerly integrated cranial modules, correlated with increased diversification in these lineages [9]. Using the body as a method of prey restraint or to outright capture prey is prominent in other vertebrates outside fishes (e.g.…”
Section: (B) Why Do Stingrays Chew?mentioning
confidence: 99%
“…), prey capture and processing may be handled by two systems-prey capture is achieved with the disc (the morphological structure derived from encircling pectoral fins [8]), leaving the jaws and teeth for prey processing. In all these cases, different anatomical modules handle different functions, allowing for independent modular evolution [9] and increased evolutionary flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have examined divergence between biting and suction feeding fishes [17,40] but few have done so in a way that incorporates multiple recent transitions (but see [41]). A previous study of New World cichlids shows an association between enhanced jaw protrusion and foraging on evasive prey, though only some of the non-evasive prey specialists in that study were biting taxa [42].…”
Section: (C) Evolution Of Fish Feeding Modesmentioning
confidence: 99%